Factors Influencing User Satisfaction with the Academic Information System (SIAKAD) Using the DeLone & McLean Model - Rahma Fitriana; Adnan Kasofi; Ringga Sentagi Asa (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
This study examines the influence of System Quality, Service Quality, and Information Quality on the usage and user satisfaction regarding the Academic Information System (SIAKAD) at U iversitas Negeri Jakarta (UNJ), utilizing the DeLone and McLean Information Systems Success Model (2003) as a conceptual framework. Although SIAKAD supports critical academic activities, it has encountered operational issues, including system disruptions and access-related complaints during course registration periods. This quantitative study employed a survey method involving 185 students from the Digital Business program (cohorts 2022–2024). Data were analyzed using Partial Least Squares Structural Equation Modeling (SEM-PLS) with SmartPLS software. The results indicate that all seven proposed hypotheses were supported: system quality, service quality, and information quality each exert a positive and significant influence on usage and user satisfaction, while usage has a positive and significant influence on user satisfaction. Information Quality emerged as the strongest predictor of Usage, whereas Usage was the strongest predictor of User Satisfaction. These findings confirm the relevance of the DeLone and McLean model in the context of an academic information system with mandatory usage, and provide empirical insights for improving the quality of SIAKAD services at Universitas Negeri Jakarta.